Production of melanin pigments in saprophytic fungi in vitro and during infection. (15th October 2019) - Chongkae, Siriporn; Nosanchuk, Joshua D.; Pruksaphon, Kritsada; Laliam, Angkana; Pornsuwan, Soraya; Youngchim, Sirida
Abstract: Melanins are one of the great natural pigments produced by a wide variety of fungal species that promote fitness and cell survival in diverse hostile environments, including during mammalian infection. In this study, we sought to demonstrate the production of melanin in the conidia and hyphae of saprophytic fungi, including dematiaceous and hyaline fungi. We showed that a melanin‐specific monoclonal antibody (MAb) avidly labeled the cell walls of hyphae and conidia, consistent with the presence of melanin in these structures, in 14 diverse fungal species. The conidia of saprophytic fungi were treated with proteolytic enzymes, denaturant, and concentrated hot acid to yield dark particles, which were shown to be stable free radicals, consistent with their identification as melanins. Samples obtained from patients with fungal keratitis due to Fusarium falciforme, Aspergillus fumigatus, Aspergillus flavus, Curvularia lunata, Exserohilum rostratum, or Fonsecaea pedrosoi were found to be intensely labeled by the melanin‐specific MAb at the fungal hyphal cell walls. These results support the hypothesis that melanin is a common component that promotes survival under harsh conditions and facilitates fungal virulence. Increased understanding of the processes of melanization and the development of methods to interfere with pigment formation may lead to novel approaches to combat these complex pathogens that are associated with high rates of morbidity and mortality.